2020
DOI: 10.1007/s00170-020-06132-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical aspects of cutting forces and tool wear in the laser-assisted turning of Ti-6Al-4V titanium alloy using AlTiN coated cutting tools

Abstract: Machining of hard-to-cut materials with conventional processes is still considered as a challenge, as the special properties of these materials often lead to rapid tool wear and reduced surface integrity. For that reason, it is preferable to combine conventional machining processes with other technologies in order to overcome the problems of machining these materials. In the present work, laser-assisted turning experiments on a Ti-6Al-4V workpiece were conducted using AlTiN coated cutting tools in order to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…This was due to the greater effect of the UAM technology at the lowest range of cutting parameters as discussed in the cutting force section. It is important to note that there is a clear correlation between the reduction of the mechanical loading and the effect on the Ra; this has been observed by other researchers [18][19][20][21][22] for Ti-6Al-4V. Furthermore, the reduction in mechanical loading might have also improved the stability of the cutting operation, and thus enhance the stiffness of the tool.…”
Section: Hybrid Turning: Surface Roughnessmentioning
confidence: 56%
See 1 more Smart Citation
“…This was due to the greater effect of the UAM technology at the lowest range of cutting parameters as discussed in the cutting force section. It is important to note that there is a clear correlation between the reduction of the mechanical loading and the effect on the Ra; this has been observed by other researchers [18][19][20][21][22] for Ti-6Al-4V. Furthermore, the reduction in mechanical loading might have also improved the stability of the cutting operation, and thus enhance the stiffness of the tool.…”
Section: Hybrid Turning: Surface Roughnessmentioning
confidence: 56%
“…In these two investigations, LAM was found to reduce cutting forces and improve surface roughness. In similar experimental LAM work on Ti-6Al-4V, Hedberg et al [20], Habrat et al [21], and Kalantari et al [22] found an improvement in tool wear and residual stresses under certain laser processing and mechanical machining conditions, without significant detrimental effect on microstructure. Feng et al [23] investigated LAM by developing an analytical model to predict residual stresses, where they considered the recrystallisation of the material due to the exposure to the laser beam.…”
Section: Introductionmentioning
confidence: 89%
“…Owing to the advantages of lasers in terms of energy concentration, fast processing, good controllability, and high accuracy, laser-assisted mechanical machining has become a research hotspot [115][116][117][118][119][120][121]. Laser-assisted mechanical machining is a hybrid process that uses a laser to reduce the physical/mechanical properties of materials or to modify the phase/microstructure of local materials to improve machinability.…”
Section: Laser-assisted Mechanical Machiningmentioning
confidence: 99%
“…As a typical difficult-to-cut material, the superalloy used for these key components usually has good comprehensive properties, such as high strength, corrosion resistance, and fatigue resistance. In the machining of such hard-to-cut alloys, high cutting temperature, serious tool wear, poor quality, and other problems are often improved by various auxiliary machining methods, such as nitrogen [ 1 ], CO 2 [ 2 ], and cooling machining, by reducing the cutting temperature to improve the surface quality [ 3 ], while the laser-assisted cutting method reduces cutting force but accelerates tool wear [ 4 ]. MQL lubrication improves surface quality, while reducing tool wear and cutting temperature, due to cooling and local lubrication of the cutting zone [ 5 ].…”
Section: Introductionmentioning
confidence: 99%